2022
DOI: 10.1002/nop2.1288
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students' experience of incivility behaviours and its correlation with their nursing professional values: A cross‐sectional descriptive study

Abstract: Incivility behaviours have been identified as one of the major problems in the clinical setting of the nursing profession. In clinical settings, nursing students face many challenges in communicating with other students, educators and nursing staff. These challenges shape their professional and social character (O'Mara, McDonald, Gillespie, Brown, & Miles, 2014). In addition to learning in a clinical setting, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Another study demonstrated a correlation between nurse’s perceptions of image and their own self esteem [ 39 ]. Factors such as media representations and relationships with colleagues also play a role in shaping the perception of nursing as highlighted by research on behaviors experienced by nursing students and its impact on ethical standards [ 37 ]. Given that perception affects aspects such as resource allocation, professional growth, employee performance, stress levels and job satisfaction, within the nursing field it is crucial for nurses to uphold a favorable image both externally and internally [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated a correlation between nurse’s perceptions of image and their own self esteem [ 39 ]. Factors such as media representations and relationships with colleagues also play a role in shaping the perception of nursing as highlighted by research on behaviors experienced by nursing students and its impact on ethical standards [ 37 ]. Given that perception affects aspects such as resource allocation, professional growth, employee performance, stress levels and job satisfaction, within the nursing field it is crucial for nurses to uphold a favorable image both externally and internally [ 13 ].…”
Section: Discussionmentioning
confidence: 99%